Existence and uniqueness of solutions for delay boundary value problems with p-Laplacian on infinite intervals - Wei, Yuming (2014)
This paper is concerned with the existence and uniqueness of solutions for boundary value problems with p-Laplacian delay differential equations on the half-line. The existence of solutions is derived from the Schauder fixed point theorem, whereas the uniqueness of solution is established by the Banach contraction principle. As an application, an example is given to demonstrate the main results.